Unconfined compressive strength performance of cement stabilized peat with rice husk ash as a pozzolan - Wong L.S. (Trans Tech Publications Ltd, 2023)
Peat is known to be highly compressible in nature due to its extremely high content of organic matter. As such, it is never a suitable foundation soil for construction purpose. Under such condition, it is compelling to investigate the underlying binding action of suitable materials that can be sustainably applied to stabilize the soil. The primary focus of this research article is to evaluate the effectiveness of rice husk ash as partial cement replacement in peat stabilization. Rice husk ash is basically a pozzolanic material which is produced by burning rice husk from the milling of paddy. Other than rice husk ash, Portland composite cement, calcium chloride, and silica sand were used as the materials for stabilizing the peat. An experimental based program was developed to gage the pertinent aspects that influenced the strength behavior of the stabilized peat. The strength behavior of the stabilized peat was evaluated on the basis of the results from unconfined compression tests. It was found from the test results that by partially replacing 10% of the cement with rice husk ash at an initial pressure of 50 kPa, binder dosage of 300 kg m-3, silica sand dosage of 596 kg m-3 and a curing time of 28 days, the required unconfined compressive strength of 345 kPa could be exceeded. The positive result confirmed the role of rice husk ash at imparting filler and pozzolanic effects that enhanced the strength of the stabilized peat. © (2014) Trans Tech Publications, Switzerland.